The Use of FTIR-ATR Spectrometry for Evaluation of Surgical Resection Margin in Colorectal Cancer: A Pilot Study of 56 Samples - Hongwei Yao; Xueying Shi; Yuanfu Zhang (Journal of Spectroscopy)
Colorectal cancer is one of the most common malignancies in human, and it is also one of the most leading causes of cancer-related death. Recently, Fourier transform infrared (FTIR) spectrometry is considered to develop into a new method for cancer diagnosis. In this study, colorectal cancer and mucosa 1 cm, 2 cm, and 5 cm away from tumor were measured by FTIR spectroscopy. FTIR spectra of colorectal cancer and mucosa 1 cm away from tumor were different from those of mucosa 2 cm and 5 cm away from tumor. According to the analysis of FTIR spectrometry, the decrease of lipid and the increase of protein and nucleic acid were observed in the former two sites. FTIR spectrometry, therefore, may be developed into a rapid promising method for judging surgical resection margin of colorectal cancer.